2021
DOI: 10.3389/fonc.2021.648968
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Biomarkers for Predicting Bladder Cancer Lymph Node Metastasis

Abstract: Bladder cancer is one of the leading causes of cancer deaths worldwide. Early detection of lymph node metastasis of bladder cancer is essential to improve patients’ prognosis and overall survival. Current diagnostic methods are limited, so there is an urgent need for new specific biomarkers. Non-coding RNA and m6A have recently been reported to be abnormally expressed in bladder cancer related to lymph node metastasis. In this review, we tried to summarize the latest knowledge about biomarkers, which predict l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…Furthermore, because of the different causative molecules, although some patients have the same TNM stage or similar risk factors, they may have different clinical outcomes. Therefore, molecular biomarkers to predict tumor prognosis are of great importance [ 24 , 25 ]. Ferroptosis may be associated with biological behaviors such as proliferation, invasion, and metastasis in BC [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because of the different causative molecules, although some patients have the same TNM stage or similar risk factors, they may have different clinical outcomes. Therefore, molecular biomarkers to predict tumor prognosis are of great importance [ 24 , 25 ]. Ferroptosis may be associated with biological behaviors such as proliferation, invasion, and metastasis in BC [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many new treatment strategies have been proposed to improve outcomes and suppress adverse events in these patients (7,8). Furthermore, the identification of better predictive markers for BC recurrence and metastasis is important, and many investigators pay special attention to this issue (9)(10)(11).…”
mentioning
confidence: 99%
“…Different from YTHDF that may accelerate mRNA decay [ 27 ], IGF2BPs, as newly identified m6A readers, can target numerous mRNAs and maintain their stability to promote cancer progression and metastasis in a m6A-dependent manner [ 28 , 29 ]. Several recent studies have reported that m6A modification is implicated in lymphatic metastasis in cancers [ 30 32 ]. However, the functional roles of IGF2BP2 in HNSCC, and more specifically whether IGF2BP2 regulates lymphatic metastasis in HNSCC by modifying m6A is currently unclear.…”
Section: Introductionmentioning
confidence: 99%